Concept analysis of community health outreach - Hye Young Shin; Ka Young Kim; Purum Kang (BMC, 2020)
Abstract Background The definition of community health outreach to promote the health of vulnerable populations depends heavily on the particulars of the given health project and community. There is no consistency in the definitions attached to the concept itself. Our study aimed to clarify the general definition of community health outreach to facilitate its understanding and use. Methods Walker and Avant's (2010) method of concept analysis was used to understand community health outreach. A total of 45 articles were included in the analysis after having searched for text on database portals like PubMed, Scopus, CINAHL complete and EMBASE published between 2010 and 2018. Results The defining attributes of the concept of community health outreach were purposive, temporary, mobile and collaboration with community. The antecedents were population facing health risks and awareness of health risks. The consequences were increased accessibility and health promotion. Conclusion This study proposed the definition of community health outreach as a temporary, mobile project that involves the collaboration of a community to undertake its purposeful health intervention of reaching a population facing health risks. This definition provides a general understanding of the outreach undertaken by health workers and enables the strong connection between health professionals and community residents.